A CBCT assessment of orthodontic mini-implant placement - A M Ashil; Aseem Sharma; Lijo K Jose; Shubhi Grover; Anuraj Singh Kochar; Shaji T Varghese; Tanushree Sharma; Prabu Mahin Syed Ismail (Journal of Pharmacy and Bioallied Sciences, 2024)
Objectives: This study compares the precision of cone beam computed tomography (CBCT) and two-dimensional radiography for mini-implant implantation. Materials and Method: For 30 sites (in 15 patients between the ages of 13 and 26 years), the buccal interradicular region among the 2nd premolar and 1st molar was found to be the best location for mini-implants. Next, two groups of the mini-implant implantation process were created. Mini-implants were positioned at the CBCT data-identified sites in the CBCT group. Mini-implants were inserted in the RVG group by using two-dimensional digital radiography and a specially constructed guide. To assess the precision of the mini-implant implantation, post-placement CBCT images were acquired. The obtained data were statistically analyzed. Result: The two groups showed a statistically considerable variation in the mini-implant placement's departure from the optimal height. Due to the smaller interradicular space and decreased convenience in the posterior mandibular area, two out of 15 mini-implants in the RVG group demonstrated root contact in the mandibular jaw. Conclusion: The two-dimensional intraoral radiograph of the interradicular area provides sufficient information for mini-implant placement even though CBCT accurately visualizes the interradicular space in three dimensions.